Rancangan Aplikasi SMS Gateway untuk Pemesanan Pendaftaran Service Sepeda Motor di AHASS XYZ - Ade Kurnia Solihin (Universitas Indraprasta PGRI Jakarta, 2018)
Astra Honda Authorized Service Station xyz (AHASS xyz) is a company engaged in the service providers maintenance and sale of spare parts specific to honda motorcycle brand. As a company engaged in the field of services, quality of service is very important to be kept and improved. To get the service of the astra's motorcycle service honda authorized service station (AHASS), is the official workshop AHASS motorcycles honda brand that caters to special care, motorcycle sales and sales of motorcycle-specific spare parts brands Honda. At AHASS xyz customers have to stand in line for quite a while because of the many customers who also want to get service service motorcycles, these conditions that make customers uncomfortable because a lot of time wasted in vain for wait queue service. The purpose of this research is to reduce the waiting time a prospect at the moment will be doing maintenance on a motorcycle at AHASS. In this system the design of the data collection method that is used for library studies, interviews and observations. Systems development methods are used, use the method waterfall, the programming language that is used in the design is the PHP and using software extension gammu and database using MySQL. Based on research done then SMS Gateway application system design for booking registration service AHASS motorcycle. You can make a good solution to overcome the problem of queues and waiting times that occur in AHASS xyz.